Life cycle costing of energy recovery from solid recovered fuel produced in MBT plants in Italy. (November 2019) - Rigamonti, Lucia; Borghi, Giulia; Martignon, Giovanna; Grosso, Mario
Highlights: An Environmental Life Cycle Costing of residual waste management was performed. The focus was on mechanical–biological treatment (MBT) plants. Two functional units were considered: 1 tonne of waste and 1 MWh of exergy. Promoting waste treatment in single-stream MBT plants reduces the costs. The use of Solid Recovered Fuel in co-combustion maximises the exergy production. Abstract: The Environmental Life Cycle Costing (LCC) methodology was applied to assess the costs of the processing in Italy of municipal Residual Waste (RW) in Mechanical-Biological Treatment (MBT) plants aimed at the production of Solid Recovered Fuels (SRFs), delivered to dedicated waste-to-energy (WTE) plants or to co-combustion. Two different functional units were defined to consider two different perspectives: 1 tonne of residual waste in input of the MBT plant, and 1 MWh of exergy produced by the energy valorisation of the streams delivered by the MBT plant. Four strategies were analysed that differ for the type of MBT (single stream or separated streams) and the destiny of the SRF (dedicated WTE plant or cement kiln). The results appear to strongly recommend the treatment of the RW in a single stream MBT plant and the production of a SRF with characteristics suitable to meet the technological, economic and environmental needs for co-combustion, substituting fossil fuels.